Limited evidence for calcium supplementation in preeclampsia prevention: a meta-analysis and systematic review. (May 2015) - Tang, Reuben; Tang, Ing Ching; Henry, Amanda; Welsh, Alec
Abstract : Objective : This article synthesises evidence for calcium supplementation in preeclampsia prevention. Methods : Major databases and trial registries were searched, and comparisons were made against other meta-analyses. Results : Calcium supplementation reduced the overall risk of preeclampsia in 10 trials ( n  = 24 787; risk ratio (RR) 0.62; 95% confidence interval [CI] 0.47–0.81). Its effect was larger in two subgroups: low-baseline calcium intake (RR 0.42 [0.23–0.76]) and increased risk of developing hypertensive disorders (RR 0.36 [0.10–0.98]). This effect was not significant amongst larger studies (RR 0.93 [0.83–1.04]). Funnel plotting suggested possible publication bias. Conclusion : Some evidence for calcium supplementation exists, but its utility is limited by the possibility of publication bias and a lack of large trials.